(untitled) (American Journal of Technology and Applied Sciences, 2024)
Relevance. The article is devoted to the issue of utility and possibilities of optical coherence tomography (OCT) in closed globe injury (CGI) in order to objectively assess the state of the optic nerve disc (OND) and the peripapillary of retinal nerve fibers layer (RNFL) of the traumatized eye. Purpose of the study: to determine the diagnostic capabilities of OCT in patients with closed globe injury (CGI) and traumatic optic neuropathy (TON) caused by contusion. Materials and Methods. A study of 30 patients, including 20 men, and 10 women aged 20 to 45 years with transparent optic media in the early period after trauma was conducted in the multispecialty clinic of Tashkent Medical Academy in the departments of emergency traumatology and neurosurgery. The control group consisted of 30 healthy individuals of similar sex and age. Results of the study. OCT allows to determine the thickness of RNFL and the degree of fiber damage in the retina and optic nerve due to the traumatic process at the earliest stage after the trauma when other traditional ophthalmologic examinations turn out to be uninformative. As a result of the study, a significant increase in macular volume, the size of OND, and the thickness of peripapillary fibers of RNFL was found on optical coherence tomography in patients with CGI compared to the control group Conclusion. Our study has shown that OCT can be used for objective assessment and diagnostics of retinal and optic nerve damage in CGI.